School TV as a Learning Media in Improving Listening Skills in Early Childhood - Ari Wulandari; Shofa; Eka Sri Pujianti; Hasmira; Sri Watini (International Conferences on Early Childhood Education Proceedings, 2024)
Digital media innovation as one of the indispensable techniques in the modern era 4.0 has developed rapidly and fluctuated affecting various parts of life in all circles, including the world of early childhood. One of the influential parts of life is language. During the pandemic, children have a lot of time with digital media. So, without realizing it, this has a huge impact on children's language development. Currently, there is one media that can answer this need, namely digital media School TV. Children, parents, and teachers can utilize the "School Stage" feature on the School TV channel in the form of streaming broadcasts. The research will center on the role of School TV, whether it has a significant impact on listening skills in early childhood, using Classroom Action Research (CAR/ PTK). The research was conducted during November-December 2023 at ABA 21 Rawamangun Kindergarten, East Jakarta. From the results of research conducted in 3 cycles. The results of perception before activities at the pre-cycle stage were 16 children ranked as not yet developing (BB/ Belum Berkembang) 3 children ranked as starting to develop (MB/ Mulai Berkembang) and 1 developing as expected (BSH/ Berkembang Sesuai Harapan) with a total percentage of 20.08% who began to develop. In Cycle I, the children's score level reached 55% in the beginning to develop (MB/ Mulai Berkembang) class, indicating that improvement was needed in Cycle II. After the second cycle was conducted, the children's average score reached 80% in the very good developing class (BSB/ Berkembang Sangat Baik).